Magnetic resonance imaging findings in painful hemiplegic shoulder patients with or without subluxation: A retrospective cohort study - Xie, Hui-Min; Zhang, Xiao-Tan; Xu, Lin; Wang, Ning; Wang, Rui; Jia, Zi-Shan; Zhang, Li-Ning (Frontiers in Neurology, 2022)
Background: The relationship between hemiplegic shoulder pain (HSP) and subluxation is unclear. This study aimed to determine the differences of magnetic resonance imaging (MRI) findings in HSP patients with or without subluxation after stroke, and to analyze the etiology of shoulder pain. Methods: This retrospective study included 53 patients with HSP after stroke from September 2013 to February 2021. Patients underwent MRI of the shoulder because of shoulder pain. Clinical characteristics, including age, sex, stroke duration, body mass index, stroke type, visual analog scale score, Brunnstrom stage, and MRI arthrography findings of the affected shoulder, were recorded. Patients were classified into the glenohumeral subluxation (GHS) group (n=27) or non-glenohumeral subluxation (nGHS) group (n=26). Results: We found that patients with HSP may be prone to bursa effusion, rotator cuff injury, ligament injury, and cartilage injury, even though there was no significant difference between the GHS and nGHS groups. MRI revealed 14 cases of long bicipital tendon-glenoid labrum injury (51.8%) in the GHS group and 6 cases (23.1%) in the nGHS group (p=0.030). We also found 10 cases (37%) of glenoid labrum injury in the GHS group and 2 cases (7.7%) in the nGHS group (p=0.026). Eight cases (29.6%) and 1 case (3.8%) of bone marrow edema were found in the GHS and nGHS groups, respectively (p=0.033). Conclusions: Compared with painful hemiplegic shoulder patients without subluxation, patients with subluxation may be more susceptible to some injuries, such as long bicipital tendon-glenoid labrum injury, glenoid labrum injury, and bone marrow edema. During rehabilitation, physicians need to pay attention to these injuries.